A shape memory ceramic reinforced aluminum-based composite material and a method for preparing the same with adjustable austenite content
By using cerium-containing zirconium dioxide single crystal particles and ball mill mixed dispersion technology in shape memory ceramics and aluminum-based composites, combined with temperature-raising insulation and sintering processes, the problem of restricted application of reversible phase change under large sizes and serious interface reactions is solved, and the preparation of shape memory ceramic reinforced aluminum-based composites with high density and high austenite content is achieved, which broadens the application range.
Patent Information
- Application Number
- CN202210560425.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-05-23
AI Technical Summary
The existing shape memory ceramics have limited applications for reversible phase change under large sizes, and they react severely at the interface with aluminum-based composite materials, making it difficult to achieve austenitization.
Single crystal particles based on cerium-containing zirconium dioxide are used as shape memory ceramics, and the austenitization is achieved through a ball mill, and the austenitization is achieved through a sintering process to regulate the austenite content.
It realizes controllable austenite phase content of shape memory ceramics at room temperature, improves the density and austenite content of composite materials, avoids interfacial reactions, retains the structural-functional integrity of the material, and broadens the application range.
Smart Images

Figure CN115570132B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal matrix composite materials, and in particular to a preparation method of a shape memory ceramic reinforced aluminum matrix composite material and an adjustable austenite content composite material. Background Art
[0002] Under the action of temperature field or force field, zirconium oxide (ZrO2) based shape memory ceramics can undergo The reversible phase change of materials can induce significant shape memory effect or superelastic effect, and has potential engineering applications such as energy dissipation and phase change toughening. It has gradually become a hot research object for the new generation of smart materials in the 21st century.
[0003] Since the 1980s, researchers have been adjusting the phase transition temperature and stress threshold of shape memory ceramics by changing the element doping (such as cerium, yttrium, magnesium, etc.), giving this type of material a continuously adjustable phase transition property. For example, Swan et al. (Nature, 1986, 322 (6076): 234-236) first discovered and reported that 9.4mol% MgO-stabilized tetragonal zirconia polycrystalline ceramics can recover 0.5% strain at 800°C. Lai et al. (Science, 2013, 341 (6153): 1505-8) found that 8% CeO2-0.5% Y2O3-ZrO2 microcolumns can achieve 50 cycles at 7% strain. On the one hand, traditional shape memory ceramics cannot overcome the intrinsic contradiction of "size-brittleness", which greatly limits their development and application prospects; on the other hand, too low a doping amount leads to a higher action temperature window of shape memory ceramics, and too high a doping amount easily leads to a decrease in energy consumption density. How to achieve controllable preparation of austenite content in shape memory ceramics at a smaller doping amount and lower operating temperature has become a major difficulty.
[0004] Since the 21st century, the application and rapid development of particle-reinforced aluminum-based composites in high-tech fields such as aerospace, national defense and military industry have provided new ideas and methods for the study of large-scale reversible phase change of shape memory ceramics. At present, there are no literature reports related to shape memory ceramics reinforced metal-based composites. And from the existing similar literature reports, the preparation methods of ZrO2 / metal mainly adopt the following two methods: one is the liquid method, such as 3D printing, stirring casting, and pressureless (pressure) infiltration method. The preparation process of this method is simple, but the disadvantage is that the preparation temperature is too high and there may be serious interface reactions (3Al+[Zr]——Al3Zr); the other is the solid-state method, such as external field-assisted sintering (flash burning, spark plasma sintering, ultrafast sintering method), the disadvantage is that the degree of densification is poor and it is difficult to design the composite configuration. For example, Abdizadeh et al. (Ceramics International, 2013, 39(2): 2045-2050) prepared 15 vol% 3YSZ particle reinforced A356 aluminum composite material by stirring casting, achieving a tensile strength of 232 MPa, but the paper did not further study its phase change effect; Zhang et al. (Materials Science and Engineering: A, 2022, 838: 142792) prepared nano ZrO2 particle reinforced AlSi10Mg composite material by selective laser melting technology, with a tensile strength of 478.6 MPa and an elongation of 10.6%, but the prepared ceramic was a monoclinic phase and there was a serious interface reaction. Summary of the invention
[0005] Aiming at the application bottleneck of reversible phase transformation of shape memory ceramics under large size, and the problem of severe interface reaction and difficulty in austenitization in the preparation process of shape memory ceramic reinforced aluminum-based composite materials, the purpose of the present invention is to provide a preparation method of shape memory ceramic reinforced aluminum-based composite materials and adjustable austenite content. Under the premise of ensuring the complete structure and performance of shape memory ceramics, the preparation method of the present invention can evenly disperse the shape memory ceramics in the composite material, and realize the controllable preparation of the austenite content of the shape memory ceramics in the composite material at room temperature.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a shape memory ceramic reinforced aluminum-based composite material, wherein the raw materials of the composite material include shape memory ceramic and aluminum powder; in the raw materials of the composite material, the mass content of the shape memory ceramic is 1 to 90%, and the remainder is aluminum powder;
[0008] The raw materials of the composite material include single crystal particles of zirconium dioxide containing cerium, and the composition includes 3-12 mol% CeO2 and the balance ZrO2. In the early experiments of the present invention, it was found that when the content of CeO2 in the shape memory ceramic is lower than 3 mol%, it is impossible to obtain a composite material with both high density and high austenite content.
[0009] Preferably, in the raw materials of the composite material, the particle size D50 of the shape memory ceramic used is 0.2-2 μm, and the proportion of the austenite phase at room temperature is 0-12.3 wt %.
[0010] Preferably, the shape memory ceramic used in the raw materials of the composite material includes: 6-12 mol% CeO2 and the balance ZrO2. Preferably, the aluminum powder is pure aluminum powder or aluminum alloy powder, and the particle size D50 of the aluminum powder is 10-100 μm.
[0011] Preferably, the shape memory ceramic in the composite material has an austenite phase ratio of 3.8-100wt% at room temperature.
[0012] Preferably, the shape memory ceramic in the composite material has an austenite phase ratio of 60-100wt% at room temperature.
[0013] The present invention also provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material, comprising the following steps:
[0014] A1. Mixing and dispersing the raw materials of the composite material, shape memory ceramic and aluminum powder, to obtain shape memory ceramic / aluminum composite powder;
[0015] A2, heating the shape memory ceramic / aluminum composite powder and then keeping the temperature to achieve austenitization;
[0016] A3. Densification processing is performed on the austenitized shape memory ceramic / aluminum composite powder to obtain a shape memory ceramic reinforced aluminum matrix composite material.
[0017] Preferably, in step A1, the mixing and dispersing step is performed by uniform-speed ball milling or variable-speed ball milling using a ball mill, the rotation speed of the ball mill is 200 to 500 rpm, and the ball milling time is not less than 3 hours.
[0018] Preferably, in step A2, the insulation temperature range is 300-600° C., and the insulation time is 1-2 hours.
[0019] Preferably, when the CeO2 content of the shape memory ceramic is greater than or equal to 3 mol% and less than or equal to 6 mol%, the insulation temperature range is 500-600°C; when the CeO2 content of the shape memory ceramic is greater than 6 mol% and less than or equal to 9 mol%, the temperature range is 400-500°C; when the CeO2 content of the shape memory ceramic is greater than 9 mol% and less than or equal to 12 mol%, the temperature range is 300-400°C.
[0020] In the inventor's previous experiments, it was found that if the holding temperature is too high, the higher the cerium content, the more likely the interface reaction will affect the performance of the shape memory ceramic; if the holding temperature is too low, the shape memory ceramic cannot be austenitized. The present invention further optimizes the holding temperature ranges used by shape memory ceramics with different CeO2 contents, thereby preparing a shape memory ceramic reinforced aluminum-based composite material with both high density and high austenite content.
[0021] Preferably, in step A2, the insulation temperature is higher than the austenite starting temperature of the shape memory ceramic.
[0022] Preferably, in step A3, the densification process adopts a sintering process, and the pressure range used in the sintering process is 300-1000 MPa. If the pressure used is too high, the mold will easily fail; if the pressure is too low, it will cause the matrix to be constrained and difficult to retain the austenite phase.
[0023] The present invention can significantly improve the austenite content of the composite shape memory ceramic through heat preservation and densification processing. The shape memory ceramic raw material with a CeO2 content of 6-12 mol% can achieve an austenite content of more than 60wt% after being prepared by the preparation method of the present invention; after using the optimized heat preservation temperature, the austenite content after composite can reach 100%.
[0024] Preferably, the sintering process is selected from any one of atmosphere sintering, vacuum hot pressing sintering, spark ion beam sintering and hot isostatic pressing sintering.
[0025] Preferably, the sintering temperature used in the vacuum hot pressing sintering is consistent with the insulation temperature, and the sintering time is 1 to 2 hours.
[0026] The present invention adopts the above-mentioned preparation method, which can evenly disperse the reinforcement particles (shape memory ceramics) in the microstructure, and can adjust the austenite content of the shape memory ceramics at room temperature in the composite material. Compared with the monomer shape memory ceramics, the austenite content is improved. At the same time, by reasonably selecting the insulation temperature, the shape memory ceramics are austenitized to a certain extent, which can avoid the interface reaction between the shape memory ceramics and aluminum, and retain the integrity of the shape memory ceramic structure-function. The sintering process adopts a suitable pressure, which can produce enough matrix constraints, so that the shape memory ceramics still maintain the austenite phase after cooling, and can give full play to the stress-induced phase change effect of the shape memory ceramics in the composite material, broaden the application range of the superelastic effect of the shape memory ceramics at room temperature, save energy and time, and are suitable for batch preparation and production.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) In the shape memory ceramic reinforced aluminum-based composite material prepared by the present invention, the shape memory ceramic is evenly dispersed, has high density, and maintains good structural integrity, and no brittle phase Al3Zr is generated.
[0029] (2) The composite material prepared by the present invention can regulate the phase content of austenite, which is beneficial to fully exert the structure and phase change effect of shape memory ceramics.
[0030] (3) The preparation method of the present invention has a wide range of applications, is energy-saving and time-saving, and has a reliable and efficient process. It overcomes the problems of intrinsic brittleness and high phase transition temperature of shape memory ceramics, realizes its large-scale preparation and application, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0032] Figure 1 A schematic diagram of a process for preparing a shape memory ceramic reinforced aluminum-based composite material according to a preferred embodiment of the present invention;
[0033] Figure 2 : is the X-ray diffraction spectrum of the sample in the embodiment of the present invention, wherein: (a) is the original shape memory ceramic single crystal; (b) is the composite powder particles obtained after ball milling; (c) is the final shape memory ceramic reinforced aluminum matrix composite material;
[0034] Figure 3 is a transmission electron microscope photo of a sample in an embodiment of the present invention, wherein: Figure 3 (a) is a transmission electron microscopy image of the shape memory ceramic reinforced aluminum matrix composite. Figure 3 (b) is a local enlarged view. Figure 3(c) is the shape memory ceramic-aluminum interface, Figure 3 (d) Figure 3 The selected area electron diffraction pattern at the circled position in (c) shows that the as-prepared shape memory ceramic is an austenite phase. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0036] The following embodiment also provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material, comprising the following steps:
[0037] A1. Mixing and dispersing the raw materials of the composite material, shape memory ceramic and aluminum powder, to obtain shape memory ceramic / aluminum composite powder;
[0038] A2, heating the shape memory ceramic / aluminum composite powder and then keeping the temperature to achieve austenitization;
[0039] A3, densifying the austenitized shape memory ceramic / aluminum composite powder to obtain a shape memory ceramic reinforced aluminum matrix composite material. Preferably, in step A1, the mixing and dispersing step is performed by uniform or variable speed ball milling using a ball mill, the speed of the ball mill is 200 to 500 rpm, and the ball milling time is not less than 3 hours.
[0040] In step A1, the mass content of shape memory ceramic in the raw materials of the composite material is 1-90%, and the remainder is aluminum powder;
[0041] The shape memory ceramic is a single crystal particle based on cerium-containing zirconium dioxide; its composition includes: 3-12 mol% CeO2 and balance ZrO2; the particle size D50 of the shape memory ceramic is 0.2-2 μm, and the proportion of austenite phase at room temperature is 0-12.3 wt%.
[0042] The aluminum powder is pure aluminum powder or aluminum alloy powder, and the particle size D50 of the aluminum powder is 10 to 100 μm.
[0043] In step A2, the insulation temperature range is 300-600° C., and the insulation time is 1-2 hours.
[0044] In step A3, the densification process adopts a sintering process, and the pressure range used in the sintering process is 300-1000MPa.
[0045] The sintering process is selected from any one of atmosphere sintering, vacuum hot pressing sintering, spark ion beam sintering and hot isostatic pressing sintering.
[0046] The above methods can be used to prepare shape memory ceramic reinforced aluminum-based composite materials, and the shape memory ceramic content in the prepared composite materials is 1-90wt%, and the austenite phase accounts for 3.8-100wt% at room temperature.
[0047] The metal powders used in the following examples are all spray-formed, and the preparation method of shape memory ceramics is based on the method described in patent number: US 2019 / 0039959 A1. Figure 1 The room temperature mechanical properties of the materials in all embodiments are tested with reference to GB / T228.1-2010.
[0048] Example 1
[0049] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), such as Figure 1 As shown, the steps are as follows:
[0050] 10.5g, 10μm pure aluminum powder (spherical powder) and 4.5g shape memory ceramic (composition includes: 12mol% CeO2 and balance ZrO2, particle size D50 is 0.5μm) were placed in a planetary ball mill, 0.15g stearic acid was added as a ball milling process control agent, under argon protection, zirconium oxide balls were used as ball milling media, the ball-to-material ratio was 10:1, and the speed was 200 rpm for 12h, and then the speed was 400 rpm for 1h to obtain shape memory ceramic / aluminum composite powder. The obtained composite powder was kept at 400℃ for 1h, degreased, annealed, and austenitized, and then vacuum hot pressed and sintered at 400℃ and 1GPa for 1h to form a block with a diameter of 18mm. Its components and properties are listed in Table 1. Figure 2 is the X-ray diffraction pattern (where: Figure 2 (a) is the raw material shape memory ceramic; Figure 2 (b) is the composite powder particles obtained after ball milling; Figure 2 (c) The final shape memory ceramic reinforced aluminum matrix composite material. Figure 3 (a) is a transmission electron microscopy image of the shape memory ceramic reinforced aluminum matrix composite. Figure 3 (b) is a local enlarged view. Figure 3 (c) is the shape memory ceramic-aluminum interface, Figure 3 (d) is the selected area electron diffraction pattern of the position indicated by the circle in (c), indicating that the prepared shape memory ceramic is an austenite phase.
[0051] Comparative Example 1
[0052] The method of this comparative example is basically the same as that of Example 1, except that the shape memory ceramic is not added in this comparative example. The composition and mechanical properties of the finally obtained matrix material are listed in Table 1.
[0053] Example 2
[0054] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 20 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), and the specific steps are basically the same as those in Example 1, except that: when preparing the shape memory ceramic / aluminum composite powder, 12 g of 10 μm pure aluminum powder (spherical powder) and 3 g of shape memory ceramic are placed in a planetary ball mill. The components and properties of the final block are shown in Table 1.
[0055] Example 3
[0056] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 10 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), and the specific steps are basically the same as those in Example 1, except that: when preparing the shape memory ceramic / aluminum composite powder, 13.5 g of 10 μm pure aluminum powder (spherical powder) and 1.5 g of shape memory ceramic are placed in a planetary ball mill. The components and properties of the final block are shown in Table 1.
[0057] Example 4
[0058] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-zinc-magnesium-copper based composite material (containing 30wt.% of shape memory ceramic, wherein the cerium doping amount is 12mol%), and the specific steps are as follows:
[0059] 10.5g, 10μm aluminum-zinc-magnesium-copper alloy powder (grade 7075 aluminum alloy) and 4.5g shape memory ceramic (composition includes: 12mol% CeO2 and balance ZrO2, particle size D50 is 0.5μm) are placed in a planetary ball mill, 0.15g stearic acid is added as a ball milling process control agent, under argon protection, zirconium oxide balls are used as ball milling media, the ball-to-material ratio is 10:1, and the speed of 200 rpm is used for ball milling for 12h, and then the speed of 400 rpm is used for ball milling for 4h to obtain shape memory ceramic / aluminum composite powder. The above composite powder is kept at 400℃ for 1h, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 400℃ and 1GPa for 1h to form a block with a diameter of 18mm. Its components and properties are listed in Table 1.
[0060] Comparative Example 2
[0061] The method of this comparative example is basically the same as that of Example 4, except that the shape memory ceramic is not added in this comparative example. The composition and properties of the finally obtained aluminum-zinc-magnesium-copper alloy are listed in Table 1.
[0062] Example 5
[0063] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), and the specific steps are basically the same as those in Example 1, except that: when preparing the shape memory ceramic / aluminum composite powder, uniform ball milling is used, the speed is 200 rpm, and the ball milling time is 12 h. The components and properties of the final block material are shown in Table 1.
[0064] Example 6
[0065] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), and the specific steps are basically the same as those in Example 1, except that: when preparing the shape memory ceramic / aluminum composite powder, uniform ball milling is used, the speed is 500 rpm, and the ball milling time is 3 hours. The components and properties of the final block material are shown in Table 1.
[0066] Example 7
[0067] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 1wt.% of shape memory ceramic, wherein the cerium doping amount is 12mol%), and the specific steps are basically the same as those in Example 1, except that: when preparing the shape memory ceramic / aluminum composite powder, 14.85g of 10μm pure aluminum powder (spherical powder) and 0.15g of shape memory ceramic are placed in a planetary ball mill. The components and properties of the final block material are shown in Table 1.
[0068] Example 8
[0069] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-copper matrix composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), the steps are as follows:
[0070] 10.5g, 10μm aluminum-copper alloy powder (grade 2024 aluminum alloy) and 4.5g shape memory ceramic (composition includes: 12mol% CeO2 and balance ZrO2, particle size D50 is 0.5μm,) are placed in a planetary ball mill, 0.15g stearic acid is added as a ball milling process control agent, under argon protection, zirconium oxide balls are used as ball milling media, the ball-to-material ratio is 10:1, and the speed is 200 rpm for 12h, and then the speed is 400 rpm for 2h to obtain a composite powder. The above composite powder is kept at 400℃ for 1h, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 400℃ and 1GPa for 1h to form a block with a diameter of 18mm. Its components and properties are listed in Table 1.
[0071] Comparative Example 3
[0072] The method of this comparative example is basically the same as that of Example 8, except that the shape memory ceramic is not added in this comparative example. The composition and properties of the aluminum-copper alloy finally obtained are listed in Table 1.
[0073] Example 9
[0074] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-copper composite material (containing 60wt.% of shape memory ceramic, wherein the cerium doping amount is 12mol%), and the specific steps are basically the same as those in Example 8, except that: when preparing the shape memory ceramic / aluminum composite powder, 6g of 10μm aluminum-copper alloy powder and 9g of shape memory ceramic are placed in a planetary ball mill. The components and properties of the final block material are shown in Table 1.
[0075] Example 10
[0076] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-copper composite material (containing 90wt.% of shape memory ceramic, wherein the cerium doping amount is 12mol%), and the specific steps are basically the same as those in Example 8, except that: when preparing the shape memory ceramic / aluminum composite powder, 1.5g of 10μm aluminum-copper alloy powder and 13.5g of shape memory ceramic are placed in a planetary ball mill. The components and properties of the final block material are shown in Table 1.
[0077] Embodiment 11
[0078] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30wt.% of shape memory ceramic, wherein the cerium doping amount is 9mol%), and the specific steps are basically the same as those in Example 1, except that: 10.5g, 10μm pure aluminum powder (spherical powder) and 4.5g shape memory ceramic (composition includes: 9mol% CeO2 and the balance ZrO2, particle size D50 is 0.5μm) are placed in a planetary ball mill. The obtained composite powder is kept at 500℃ for 1h, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 500℃ and 300MPa for 1h to form a block with a diameter of 18mm. The components and properties of the final block obtained are shown in Table 1.
[0079] Example 12
[0080] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30wt.% of shape memory ceramic, wherein the cerium doping amount is 6mol%), and the specific steps are basically the same as those in Example 1, except that: 10.5g, 10μm pure aluminum powder (spherical powder) and 4.5g shape memory ceramic (composition includes: 6mol% CeO2 and balance ZrO2, particle size D50 is 0.5μm) are placed in a planetary ball mill. The obtained composite powder is kept at 600℃ for 1h, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 600℃ and 300MPa for 1h to form a block with a diameter of 18mm. The components and properties of the final block obtained are shown in Table 1.
[0081] Embodiment 13
[0082] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30wt.% of shape memory ceramic, wherein the cerium doping amount is 6mol%), and the specific steps are basically the same as those in Example 1, except that: 10.5g, 10μm pure aluminum powder (spherical powder) and 4.5g shape memory ceramic (composition includes: 6mol% CeO2 and balance ZrO2, particle size D50 is 0.5μm) are placed in a planetary ball mill. The obtained composite powder is kept at 500℃ for 1h, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 500℃ and 300MPa for 1h to form a block with a diameter of 18mm. The components and properties of the final block obtained are shown in Table 1.
[0083] Embodiment 14
[0084] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), and the specific steps are basically the same as those in Example 1, except that the obtained composite powder is kept at 300°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 300°C and 1 GPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0085] Embodiment 15
[0086] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30wt.% of shape memory ceramic, wherein the cerium doping amount is 9mol%), and the specific steps are basically the same as those in Example 1, except that 10.5g of 10μm pure aluminum powder (spherical powder) and 4.5g of shape memory ceramic (composition includes: 9mol% CeO2 and balance ZrO2, particle size D50 is 0.5μm) are placed in a planetary ball mill. The components and properties of the final block material are shown in Table 1.
[0087] Example 16
[0088] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 6 mol%), and the specific steps are basically the same as those in Example 1, except that 10.5 g of 10 μm pure aluminum powder (spherical powder) and 4.5 g of shape memory ceramic (composition includes: 6 mol% CeO2 and the balance ZrO2, particle size D50 is 0.5 μm) are placed in a planetary ball mill. The components and properties of the final block material are shown in Table 1.
[0089] Embodiment 17
[0090] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30wt.% of shape memory ceramic, wherein the cerium doping amount is 3mol%), and the specific steps are basically the same as those in Example 1, except that 10.5g of 10μm pure aluminum powder (spherical powder) and 4.5g of shape memory ceramic (composition includes: 3mol% CeO2 and the balance ZrO2, particle size D50 is 0.5μm) are placed in a planetary ball mill. The components and properties of the final block material are shown in Table 1.
[0091] Embodiment 18
[0092] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 3 mol%), and the specific steps are basically the same as those of Example 17, except that the obtained composite powder is kept at 600°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 600°C and 600 MPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0093] Embodiment 19
[0094] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 9 mol%), and the specific steps are basically the same as those of Example 11, except that the obtained composite powder is kept at 500°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 500°C and 600 MPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0095] Embodiment 20
[0096] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 6 mol%), and the specific steps are basically the same as those of Example 12, except that the obtained composite powder is kept at 650°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 650°C and 300 MPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0097] Embodiment 21
[0098] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 6 mol%), and the specific steps are basically the same as those of Example 12, except that the obtained composite powder is kept at 300°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 300°C and 300 MPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0099] Embodiment 22
[0100] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 6 mol%), and the specific steps are basically the same as those of Example 12, except that the obtained composite powder is kept at 600°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 600°C and 100 MPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0101] Embodiment 23
[0102] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), and the specific steps are basically the same as those of Example 14, except that the obtained composite powder is kept at 250°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 250°C and 1 GPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0103] Embodiment 24
[0104] This embodiment provides a method for preparing a shape memory ceramic reinforced aluminum-based composite material (containing 30 wt.% of shape memory ceramic, wherein the cerium doping amount is 12 mol%), and the specific steps are basically the same as those of Example 14, except that the obtained composite powder is kept at 550°C for 1 hour, degreased, annealed, and austenitized, and then vacuum hot-pressed and sintered at 550°C and 1 GPa for 1 hour to form a block with a diameter of 18 mm. The components and properties of the final block are shown in Table 1.
[0105] Table 1 Composition, room temperature mechanical properties and austenite content of composite materials
[0106]
[0107]
[0108] By comparing the results of Examples 12, 13, 20 and 21 in Table 1, it can be seen that when the cerium doping amount in the shape memory ceramic is 6 mol%, the austenite content after composite can be the highest, reaching 100%, when the temperature is 600°C for insulation and hot pressing sintering; when the temperature is 500°C, the austenite content after composite can reach 63.7%; and when the temperature is 650°C or 300°C, austenite cannot be obtained due to severe interface reaction and low phase change driving force, respectively.
[0109] Comparison of the results of Examples 12 and 22 shows that when the hot pressing sintering pressure in Example 21 is 100 MPa, the austenite content after compounding is only 28.7%, which is significantly lower than that of Example 12.
[0110] Comparison of the results of Examples 11 with those of Examples 15 and 19 shows that when the cerium doping amount in the shape memory ceramic is 9 mol%, the austenite content after composite can be further increased to 100% when the temperature of heat preservation and hot pressing sintering is 500°C.
[0111] Table 1 also provides the hardness results of the composite materials prepared in each embodiment. From the application perspective, it can be seen that the higher the hardness, the more conducive it is to load-bearing from a structural perspective, and the more conducive it is to inducing austenite phase transformation and exerting phase transformation potential through load transfer from a functional perspective.
[0112] The interface bonding properties of the shape memory ceramic reinforced aluminum-based composite materials prepared in the above-listed embodiments are basically the same. The shape memory ceramic reinforced aluminum-based composite material and the preparation method of the adjustable austenite content described in the present invention, under the premise of uniformly dispersing the shape memory ceramic, obtains a composite material with different austenite contents at room temperature by adjusting the temperature. Compared with the monomer shape memory ceramic, the austenite content is improved, the structural-functional integrity of the shape memory ceramic can be protected to the maximum extent, and the large-scale preparation and application of the shape memory ceramic can be realized, which broadens the application scope of the phase change of the shape memory ceramic at room temperature, saves energy and time, is safe and easy, and has the potential for large-scale application.
[0113] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a shape memory ceramic reinforced aluminum-based composite material, characterized in that: The raw materials of the composite material include shape memory ceramics and aluminum powder; in the raw materials of the composite material, the mass content of the shape memory ceramics is 1 to 90%, and the remainder is aluminum powder; The raw materials of the composite material include single crystal particles of shape memory ceramics based on zirconium dioxide containing cerium; the composition includes: 3-12 mol% CeO2 and the balance ZrO2; The method for preparing the shape memory ceramic reinforced aluminum-based composite material comprises the following steps: A1. Mixing and dispersing the raw materials of the composite material, shape memory ceramic and aluminum powder, to obtain shape memory ceramic / aluminum composite powder; A2, heating the shape memory ceramic / aluminum composite powder and then keeping the temperature to achieve austenitization; A3. Densification processing is performed on the austenitized shape memory ceramic / aluminum composite powder to obtain a shape memory ceramic reinforced aluminum matrix composite material.
2. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 1, characterized in that: In the raw materials of the composite material, the particle size D50 of the shape memory ceramic used is 0.2-2 μm, and the proportion of the austenite phase at room temperature is 0-12.3 wt%.
3. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 1, characterized in that: The aluminum powder is pure aluminum powder or aluminum alloy powder, and the particle size D50 of the aluminum powder is 10 to 100 μm.
4. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 1, characterized in that: The shape memory ceramic in the composite material has an austenite phase proportion of 3.8-100wt% at room temperature.
5. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 1, characterized in that: In step A1, the mixing and dispersing step is performed by uniform-speed ball milling or variable-speed ball milling using a ball mill, the rotation speed of the ball mill is 200 to 500 rpm, and the ball milling time is not less than 3 hours.
6. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 1, characterized in that: In step A2, the insulation temperature range is 300-600° C., and the insulation time is 1-2 hours.
7. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 6, characterized in that: When the CeO2 content of the shape memory ceramic is greater than or equal to 3 mol% and less than or equal to 6 mol%, the temperature range of insulation is 500-600°C; when the CeO2 content of the shape memory ceramic is greater than 6 mol% and less than or equal to 9 mol%, the temperature range is 400-500°C; when the CeO2 content of the shape memory ceramic is greater than 9 mol% and less than or equal to 12 mol%, the temperature range is 300-400°C.
8. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 1, characterized in that: In step A3, the densification process adopts a sintering process, and the pressure range used in the sintering process is 300-1000MPa.
9. The method for preparing the shape memory ceramic reinforced aluminum-based composite material according to claim 8, characterized in that: The sintering process is selected from any one of atmosphere sintering, vacuum hot pressing sintering, spark ion beam sintering and hot isostatic pressing sintering.
Citation Information
Patent Citations
Shape Memory Ceramic Particles and Structures Formed Thereof
US20190039959A1
Composite material made of metal and ceramic, and method for production thereof
WO2008071184A2
Cited By
Phase change induced plastic metal ceramic and preparation method thereof
CN120866672A